Arbuscular mycorrhizal fungi and aphids interact by changing host plant quality and volatile emission. (31st October 2013) - Babikova, Zdenka; Gilbert, Lucy; Bruce, Toby; Dewhirst, Sarah Y.; Pickett, John A.; Johnson, David; Field, Katie
Summary Most plants interact with both arbuscular mycorrhizal (AM) fungi, which increase nutrient acquisition, and herbivores such as aphids, which drain nutrients from plants. Both AM fungi and aphids can affect plant metabolic pathways and may influence each other by altering the condition of the shared host plant. This study tests simultaneously the effects of AM fungi on interactions with aphids (bottom‐up effects) and the effects of aphids on interactions with AM fungi (top‐down effects). We hypothesized that: (i) attractiveness of plants to aphids is regulated by induced changes in production of plant volatile organic compounds (VOCs) triggered by AM fungi or aphids; (ii) aphids reduce AM fungal colonization; and (iii) AM fungal colonization affects aphid development. Broad beans were exposed to AM fungi, aphids and a combination of both. To test for the strength of bottom‐up and top‐down effects, separate treatments enabled establishment of mycorrhizas either before or after aphids were added to plants. VOCs produced by plants were used to (i) test their attractiveness to aphids and (ii) identify the semiochemicals causing attraction. We also measured plant growth and nutrition, AM fungal colonization and aphid reproduction. AM fungi increased the attractiveness of plants to aphids, and this effect tended to prevail even for aphid‐infested plants. However, both attractiveness and aphid population growth depended on the timing of AM fungal inoculation. AM fungi suppressed emission of the sesquiterpenes (E)‐caryophyllene and (E)‐β‐farnesene, and aphid attractiveness to VOCs was negatively associated with the proportion of sesquiterpenes in the sample. Emission of (Z)‐3‐hexenyl acetate, naphthalene and (R)‐germacrene D was regulated by an interaction between aphids and AM fungi. Aphids had a negative effect on mycorrhizal colonization, plant biomass and nutrition. Our data show that below‐ and above‐ground organisms can interact by altering the quality of their shared host plant even though there is no direct contact between them. Plant interactions with herbivores and AM fungi operate in both directions: AM fungi have a key bottom‐up role in insect host location by increasing the attractiveness of plant VOCs to aphids, whereas aphids inhibit formation of AM symbioses.